Phosphoprotein Biosensors for Monitoring Pathological Protein Structural Changes. Issue 5 (May 2020) - Ahmed, Mostak; Koo, Kevin M.; Mainwaring, Paul N.; Carrascosa, Laura G.; Trau, Matt
Abstract : Current biotechnological developments are driving a significant shift towards integrating proteomic analysis with landmark genomic, methylomic, and transcriptomic data to elucidate functional effects. For the majority of proteins, structure and function are closely intertwined. Post-translational protein modifications (e.g., phosphorylation) leading to aberrantly active structures can originate a wide variety of pathological conditions, including cancer. Analysis of protein structure variants is thus integral to the identification of clinically actionable targets and the design of novel disease diagnosis and therapy approaches. However, it is still challenging to interrogate subtle structural changes of proteins in a rapid and cost-effective manner with current tools. This review primarily compiles the latest biosensing techniques for protein structural analysis. Highlights: In general, protein structure and function are intrinsically tangled, and protein phosphorylation is a key regulation of structural changes. Aberrantly function-active protein structures (due to constitutive phosphorylation) are frequently implicated in disease pathways. Advanced biosensing tools will allow better understanding of the protein molecular landscape in diseases and aid in diagnostics development for improved disease management. Importantly, there have been recent biotechnological advances in biosensors employed for the study and detection of protein structural changes associated with aberrant phosphorylation.